Method for Determining the Number of Maintenance Personnel - Wijaya, Andi Rahadiyan (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Reducing the number of workers (downsizing) is a strategic step for companies to increase their competitiveness. With downsizing, worker productivity is expected to increase; therefore, the company's financial performance can improve. For the quantitative accuracy of downsizing to be achieved, it is necessary to measure the workload of the related work. Measuring the workload on maintenance work is difficult because of the varying nature of the work activities (e.g., frequency, duration, complexity). This study aims to develop a method for calculating the number of workers working in maintenance. The developed method is based on a combination of time study and RAM (Reliability, Availability, Maintainability) methods. The number of maintenance workers is determined by calculating the Full-time equivalent value (the ratio between the actual total working hours and the maximum scheduled working hours). A full-time equivalent value greater than one indicates a workload that is too large (over-utilized), and a full-time equivalent value of less than one indicates a workload that is too small (underutilized). The method developed was then tested in a case study on maintenance work at a mining company. The results show that the proposed method can be used as input for decision-makers in determining the number of workers on maintenance work.